Hsp83/Hsp90 Physically Associates with Insulin Receptor to Promote Neural Stem Cell Reactivation. - Huang, J.; Wang, H. (Stem cell reports, 2018)
Neural stem cells (NSCs) have the ability to exit quiescence and reactivate in response to physiological stimuli. In the Drosophila brain, insulin receptor (InR)/phosphatidylinositol 3-kinase (PI3K)/Akt pathway triggers NSC reactivation. However, intrinsic mechanisms that control the InR/PI3K/Akt pathway during reactivation remain unknown. Here, we have identified heat shock protein 83 (Hsp83/Hsp90), a molecular chaperone, as an intrinsic regulator of NSC reactivation. Hsp83 is both necessary and sufficient for NSC reactivation by promoting the activation of InR pathway in larval brains in the presence of dietary amino acids. Both Hsp83 and its co-chaperone Cdc37 physically associate with InR. Finally, reactivation defects observed in brains depleted of hsp83 were rescued by over-activation of the InR/PI3K/Akt pathway, suggesting that Hsp83 functions upstream of the InR/PI3K/Akt pathway during NSC reactivation. Given the conservation of Hsp83 and the InR pathway, our finding may provide insights into the molecular mechanisms underlying mammalian NSC reactivation.